Descriptive Analysis of Epidemiological Profile from Authors of Civil Claims Due to Supposed Medical Malpractice Against Neurosurgeons In Brazil - Flores, Leandro Pretto; de Oliveira, Walduy Fernandes (Arquivos Brasileiros de Neurocirurgia: Brazilian Neurosurgery, 2020)
Introduction The neurosurgical practice often involves situations that require rapid and immediate decision making, and a very low margin for error may eventually lead to an unsatisfactory clinical outcome. Thus, neurosurgery is considered as a medical specialty with high risk for the occurrence of litigation for supposed malpractice. The main objective of the present study was to identify the most prevalent epidemiological profile of the authors of civil claims for alleged malpractice against neurosurgeons, as well as to identify the legal strategies most commonly employed in this type of lawsuit.Methods This is a descriptive, retrospective and quantitative study, with review of the initials/exordials of all civil actions motivated by alleged malpractice against neurosurgeons, defended by an office specialized in Medical Law, from 2008 to 2018. Data were collected relative to the author of the action; the disease that led to the outbreak of the action; and some legal information of interest for the outcome of the litigation.Results During the period studied, 16 compensation/eviction claims were identified as being motivated by supposed neurosurgical malpractice. The average age of the authors was 51 years old; with a high school or undergraduate level of education in 75% of the cases, and especially from the Class B social extract (43%). Degenerative affections of the lumbar spine (12 cases, 75%) were the most common diseases that motivated the litigation, followed by brain tumors (2 cases, 12.5%), 1 case of carpal tunnel syndrome, and 1 case of chronic pain due to inflammatory radiculitis. The average value of the sponsored claim was 649,000.00 reais. Justice gratuity was granted in 80% of the cases and the reversal of the burden of proof by 30%. The main documentary evidence was medical reports – from third parties or the surgeon him/herself, and medical records.Conclusions The number of civil claims against neurosurgeons has been increasing dramatically over the past decade. The results of the present study may be useful to health professionals and law offices specialized in professional defense to identify some more effective measures regarding the prevention of potential litigation, in spite of the identification of the most common personal profiles that end up proposing a process of civilian repair against neurosurgeons.
Keywords: medical malpractice; neurosurgery; civil action; justice; accountability